ANALISIS KESALAHAN PENGGUNAAN TANDA BACA DALAM MENULIS KARANGAN PESERTA DIDIK SD NEGERI 30 TALANG KELAPA - Jadidah, Ines Tasya; Okta Bela, Wulan; Pramudita, Vanesha Putri; Amalia, Amalia; Nurhaliza Fatnasari, Rheina (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2022)
This study aims to investigate the use of punctuation errors in students' essay writing at SD Negeri 30 Talang Kelapa. The research method used was descriptive qualitative research. Data were collected through interviews, tests in the form of essay writing tasks, and documentation. The research subjects consisted of 10 students. The results showed that although the learners had a good understanding of the use of punctuation marks, there were still many errors in their essay writing. The errors found included improper placement of full stops, incorrect use of capital letters, and misuse or negligence in the use of other punctuation marks. In conclusion, it is recommended that educators provide specialised guidance in the use of punctuation to learners and use creative and diverse learning methods. Constructive feedback also needs to be given to learners to help them improve their writing skills. The most common errors were inappropriate placement of full stops at the end of sentences, incorrect use of capital letters, and inappropriate use of comma punctuation. By getting the right feedback, learners can correct and improve their writing skills.